A comparative analysis of work motivation between western and islamic perspectives - Nursuria, Mahrif. (Universiti Malaysia Sarawak (UNIMAS), 2002)
The objectives of this project paper are to study the similarities and difference of work motivation in the perspectives of Western and Muslim in terms of definitions, rewards / appraisals and punishments, evaluation of both Western and Islamic theories, and the implications of work motivation to management.